TRANSLATION CHALLENGES OF IDIOMATIC EXPRESSIONS BETWEEN ENGLISH AND UZBEK - Qurbonova Malohat Jalil qizi (New modern researchers: modern proposals and solutions, 2025)
This article presents thoughts and comments on the difficulties of translating idiomatic expressions in English and Uzbek.